Analisis Efektivitas Iklan Instagram sebagai Media Promosi UMKM Brown Bottle Coffee di Jakarta - Aisyah Nur Iman Dwi Putri; Purwatiningsih Purwatiningsih; Ratih Setyo Rini (Institut Nalanda, 2025)
The development of social media is currently increasingly rapid, marked by the increasing number of internet users in Indonesia. The large number of social media followers is a problem found by several coffee shop SMEs in assessing how effective advertising is via social media, where with almost the same menu list as REN Coffee & Eatery at the same time as Brown Bottle Coffee joined Instagram in September 2020, there are differences in the number of followers on their respective Instagrams, for REN Coffee & Eatery it has 16,600 Instagram followers, but Brown Black Coffee only has 14,600 Instagram followers. Through this research, the author aims to determine the level of effectiveness of Brown Bottle Coffee Instagram advertising. Based on the research results, the largest dimension score is 4.37 for the persuasion dimension. The persuasion dimension (Persuasion) shows that the promotion carried out by SMEs using Instagram was successful in attracting interest and building the trust of respondents to decide to buy the product provided. The promotion was effective in convincing consumers, because it did not only rely on images, but also videos. The EPIC rate for all dimensions based on the EPIC model is 4.30.